EFEKTIVITAS PELAKSANAAN PERATURAN DAERAH NOMOR 10 TAHUN 2006 TENTANG SUMBER DAYA AIR DAN SUMUR - Joko Santoso; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The development of the growing construction in Pekanbaru quite rapidly, it can be seen from the many buildings that stooded in Pekanbaru City. Tampan Sub-District is one of District in Pekanbaru City with the larges area and population in Pekanbaru City, and then Tampan Sub-District is one of district that have highest number of buildings compared to other Sub-Districts in Pekanbaru City. In case, that the buildings doesn’t have absorbtion wells as required in Pekanbaru City Regional Regulation No. 10 year of 2006 about Water Resources and Infiltration Wells.The purpose of this research was to determine and analyze the implementation of Pekanbaru City Regional Regulation No. 10 year of 2006 about Water Resources and Infiltration Wells (Case Study in Tampan Sub-District). The theory in this research used organizational effectiveness by Richard M. Steers. The research method used qualitative research, with the technique of interviews by key informants of Dinas Tata Ruang dan Bangunan and people that having Ruko and Buildings in Tampan Sub-District.Based on the research conducted, the implementation of Pekanbaru City Regional Regulation No. 10 year of 2006 about Water Resources and Infiltration Wells (Case Study in Tampan Sub-District) hasn’t been effectively implemented by the Dinas Tata Ruang dan Bangunan of Pekanbaru City. Because there are showed still many Ruko and Buildings in Tampan Sub-Disctrict doesn’t make infiltration wells around the building.Keywords: Effectivity, Regulatory Areas, Infiltration Wells